Lack of focus on nutrition and documentation in nursing homes, home care- and home nursing: the self-perceived views of the primary care workforce - S. J. Håkonsen; P. U. Pedersen; A. Bygholm; C. N. Thisted; M. Bjerrum (BMC, 2019)
Abstract Background Malnutrition is a comprehensive challenge for the nursing home, home care- and home nursing sector. Nutritional care and the subsequent documentation are a common and multifaceted healthcare practice that requires that the healthcare professionals possess complex combinations of competencies in order to deliver high-quality care and treatment. The purpose of this study was to investigate how a varied group of healthcare professionals' perceive their own competencies within nutrition and documentation and how organizational structures influence their daily work and the quality of care provided. Methods Two focus groups consisting of 14 healthcare professionals were conducted. The transcribed focus group interviews was analyzed using the qualitative content analysis approach. Results Six categories were identified: 1) Lack of uniform and systematic communication affect nutritional care practices 2) Experience-based knowledge among the primary workforce influences daily clinical decisions, 3) Different attitudes towards nutritional care lead to differences in the quality of care 4) Differences in organizational culture affect quality of care, 5) Lack of clear nutritional care responsibilities affect how daily care is performed and 6) Lack of clinical leadership and priorities makes nutritional care invisible. Conclusions The six categories revealed two explanatory themes: 1) Absent inter- and intra-professional collaboration and communication obstructs optimal clinical decision-making and 2) quality deterioration due to poorly-established nutritional care structure. Overall, the two themes explain that from the healthcare professionals' point of view, a visible organization that allocates resources as well as prioritizing and articulating the need for daily nutritional care and documentation is a prerequisite for high-quality care and treatment. Furthermore, optimal clinical decision making among the healthcare professionals are compromised by imprecise and unclear language and terminology in the patients' healthcare records and also a lack of clinical guidelines and standards for collaboration between different healthcare professionals working in nursing homes, home care or home nursing. The findings of this study are beneficial to support organizations within these settings with strategies focusing on increasing nutritional care and documentation competencies among the healthcare professionals. Furthermore, the results advocate for the daily involvement and support of leaders and managers in articulating and structuring the importance of nutritional care and treatment and the subsequent documentation.